Erythrocyte sedimentation rate as an osteoporosis risk factor in patients with active Crohn’s disease - Siggelkow, H.; Cortis, J.; Claus, Ch.; Funke, M.; Nolte, W.; Hü fner, M.; Raddatz, D. (Osteologie, 2009)
Crohn’s disease (CD) is associated with reduced bone mineral density and increased fracture risk. To assess the effects of the inflammatory process itself on bone parameters, we investigated patients with active CD and in remission without glucocorticoid treatment four weeks prior to analysis. Patients with active CD were compared to age-and sex-matched healthy volunteers and osteoporosis patients. Bone mineral density, bone formation and resorption markers were assessed, in addition to simple inflammatory markers and cytokines. Out of seven patients with active disease, three had osteopenia and one osteoporosis (WHO definition). The erythrocyte sedimentation rate (ESR) was associated with BMD at the femoral neck (R2 = 0.853, p < 0.01) and the spine (R2 = 0.772, p < 0.05). ESR seems to influence bone formation, as shown by lower bone alkaline phosphatase with high ESR (R2 = 0.725, R = – 0.852, p < 0.05). The clinical disease activity score was not useful in determining patients’ risk of acquiring bone disease. In conclusion, in patients with Crohn’s disease, the degree of the inflammatory process as assessed by ESR indicates bone loss and might be of value in identifying patients at risk of developing osteoporosis.
Keywords: Crohn’s disease; osteoporosis; risk factors; ESR